Effects of the extracellular matrix on myelin development and regeneration in the central nervous system. (April 2021) - Su, Min; Soomro, Shahid Hussain; Jie, Jifu; Fu, Hui
Highlights: The macromolecules that make up ECM can be divided into four categories: collagen, glycosaminoglycans, non-collagen glycoproteins, and elastin. The ECM exerts biological effects by interacting with growth factors, signal receptors or adhesion molecules. The changes of ECM indicate that it plays different functions in the entire developmental stage and pathological condition of myelin. Understanding the regulatory role of ECM in health and diseased states will accelerate the development of novel therapies for demyelinating diseases. Abstract: Extracellular matrix (ECM) is a collection of extracellular molecules secreted by cells, providing structural and biochemical support for surrounding tissues. The ECM exerts biological effects by interacting with growth factors, signal receptors or adhesion molecules. In the case of myelin formation and regeneration, the combination of ECM and its receptors (for example, integrins) modulates signaling pathways such as PI3K, MAPK, etc., which in turn induces complex biological effects throughout various stages of myelination and regeneration. Studies have also found that myelin injury would cause changes in ECM composition and thus affecting the myelin regeneration process. Research on the ECM will provide a better understanding of how myelin is formed and regenerated, which will help to develop new therapies for demyelinating diseases. Future progress in this field will provide important information on how to modify the ECM to promote proliferation and differentiation of oligodendrocyte precursor cells (OPC), thereby stimulating myelin formation and regeneration and restoring normal neural function.